Accounting and gender revisited - Broadbent, Jane; Kirkham, Linda (Accounting, auditing & accountability journal, 2008)
This e-book explores the limitations of women in the accounting sector and the complexities of gender. It uses feminist methodologies, experiences of motherhood and work and cultural differences to explore this theme.
Keywords: Accounting : Research; Accounting : Social aspects